2005
DOI: 10.1007/s10719-005-0845-9
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a soluble recombinant human ST6Gal I functionally expressed in Escherichia coli

Abstract: A soluble and active form of recombinant human ST6Gal I was expressed in Escherichia coli. The gene encoding the soluble form of ST6Gal I lacking the membrane and cytosolic regions was introduced into a bacterial expression vector, pMAL-p2X, fused in frame with a maltose-binding protein (MBP) tag. Low-temperature cultivation at 13 degrees C during IPTG-induction significantly improved both solubility and MBP-tagging of the recombinant enzyme expressed in bacteria. The supernatant prepared by disruption of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 58 publications
2
22
1
Order By: Relevance
“…Previous studies with induced protein expression in E. coli indicated that decreasing the culture temperature and using a longer induction time markedly increased target protein expression (Weickert et al 1997;Kagawa et al 2003;Hidari et al 2005). The present study demonstrates that the expression of the soluble form of the fusion protein His-GLP-N was significantly increased by decreasing the induction temperature from 37 to 268C (Fig.…”
Section: Expression and Determination Of The His-glp-n Fusion Proteinsupporting
confidence: 62%
“…Previous studies with induced protein expression in E. coli indicated that decreasing the culture temperature and using a longer induction time markedly increased target protein expression (Weickert et al 1997;Kagawa et al 2003;Hidari et al 2005). The present study demonstrates that the expression of the soluble form of the fusion protein His-GLP-N was significantly increased by decreasing the induction temperature from 37 to 268C (Fig.…”
Section: Expression and Determination Of The His-glp-n Fusion Proteinsupporting
confidence: 62%
“…We do not know exactly why high levels of the soluble form exhibited weak sialyltransferase activity (Fig. 3); however, there has been one report in which the soluble form of ST6Gal I showed weak enzymatic activity when compared with its proform (27).…”
Section: Mol Cancer Res 2008;6(8) August 2008mentioning
confidence: 94%
“…Other than unselective α2–6-sialylation of terminal and internal Gal or GalNAc residues by Pd2,6ST, 10, 12, 16, 17, 21 several other reported bacterial α2–6STs 2628 including those from GT80 family have not been tested for sialylation of poly-LacNAc-type structures. While hST6Gal-I was able to be expressed in E. coli cells at a level of 0.266 mg purified enzyme per liter culture by N-terminal truncation with fusing to maltose-binding protein (MBP) 29 and the expression level was improved to 2 mg purified protein per liter culture by co-expression of multiple chaperon/foldases in the Origami2(DE3) strain, 30 the amount was still limited for large-scale synthetic purposes.…”
Section: Introductionmentioning
confidence: 99%